2020
DOI: 10.3168/jds.2019-17619
|View full text |Cite
|
Sign up to set email alerts
|

Matrine and baicalin inhibit apoptosis induced by Panton-Valentine leukocidin of Staphylococcus aureus in bovine mammary epithelial cells

Abstract: It was previously thought that the Panton-Valentine leukocidin (PVL) toxin of Staphylococcus aureus (S. aureus) was not the main cause of cow mastitis. However, in recent years, detection of the gene encoding PVL has been increasing in dairy cow mastitis, which implies that PVL may be related to bovine mastitis. Therefore, we wanted to search for drugs inhibiting PVL or PVL-induced apoptosis. In this report, we investigated the apoptosis mechanism of PVL in bovine mammary epithelial cells (BMEC) and the inhibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 27 publications
(26 reference statements)
0
15
0
Order By: Relevance
“…The number of apoptotic cells and necrotic cells in scFv treatment groups decreased approximately by half (from 1300 to 750 in USA300 group (p < 0.01), from 1240 to 640 in ATCC25923 group (p < 0.01) and from 1590 to 860 in XD69 group (p < 0.01), respectively) compared with that of the NC group. Previous studies demonstrated that Panton-Valentine leucocidin and enterotoxin H of S. aureus could induce apoptosis of bovine mammary epithelial cells [60,61].…”
Section: Discussionmentioning
confidence: 99%
“…The number of apoptotic cells and necrotic cells in scFv treatment groups decreased approximately by half (from 1300 to 750 in USA300 group (p < 0.01), from 1240 to 640 in ATCC25923 group (p < 0.01) and from 1590 to 860 in XD69 group (p < 0.01), respectively) compared with that of the NC group. Previous studies demonstrated that Panton-Valentine leucocidin and enterotoxin H of S. aureus could induce apoptosis of bovine mammary epithelial cells [60,61].…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, it has been reported that the Panton-Valentine leukocidin (PVL) toxin of Staphylococcus aureus may be related to the pathogenic mechanism of bovine mastitis. Jia et al found that MT inhibited PVL-induced apoptosis of bovine mammary epithelial cells (BMEC) by down-regulating the expression of cleaved caspase-3, cleaved caspase-8, and cleaved caspase-9 proteins (Jia et al, 2020). Furthermore, a subinhibitory concentration of MT inhibited the Staphylococcus aureus secretion of a-hemolysin in a none dose-dependent manner, thus reducing the inflammatory damage of a-hemolysininduced BMEC cells (Feng et al, 2018).…”
Section: Antimicrobial Effect Of Mtmentioning
confidence: 99%
“…BMECs were preserved in our laboratory, the cell line (BMECs) was obtained from Shandong Agricultural University, Tai’an, China [ 22 ]. BMECs were incubated in Dulbecco’s modified Eagle’s medium (DMEM) (Biological Industries, Israel) supplemented with 10% FBS (v/v) (Gibco, Waltham, MA, USA), 5 μg/mL insulin (Sigma-Aldrich, St. Louis, MO, USA), 5 μg/mL transferrin (Sigma-Aldrich), 1 μg/mL hydrocortisone (Sigma-Aldrich), 1 μg/mL corporin (Sigma-Aldrich), and 100 U/mL penicillin-streptomycin (Sigma-Aldrich) in an environment of 5% CO 2 and 95% air at 37°C.…”
Section: Methodsmentioning
confidence: 99%
“…Fluorescent quantitative PCR was performed according to the procedure described in the ChamQ Universal SYBR qPCR Master Mix kit (Vazyme). The 2- ΔΔCq method was used to analyze the expression of target genes, and β-actin was used as an internal reference [ 22 ]. Primer design for qPCR is shown in Table 2 [ 22 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation